Herpesvirus Infections and Transglutaminase Type 2 Antibody Positivity in Childhood: The Generation R Study. Issue 4 (October 2016) - Jansen, Michelle A.E.; van den Heuvel, Diana; van der Zwet, Kirsten V.M.; Jaddoe, Vincent W.V.; Hofman, Albert; Escher, Johanna C.; Fraaij, Pieter L.A.; Hooijkaas, Herbert; van Zelm, Menno C.; Moll, Henriette A.
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Objectives: Persistent viral infections have been implicated in the etiology of autoimmune diseases in adulthood, but it is not known whether herpesviruses are associated with the development of celiac disease autoimmunity in childhood. We assessed whether herpesvirus infections are associated with transglutaminase type 2 antibody (TG2A) concentrations in children at 6 years of age. Methods: The present study was embedded within a population-based prospective cohort study. Serum immunoglobulin G levels against Epstein-Barr virus, cytomegalovirus (CMV), and herpes simplex virus type 1 were measured by enzyme-linked immunosorbent assay, and TG2A concentrations with fluorescence enzyme immunoassay in 4420 children at 6 years of age. Children were categorized based on TG2A concentrations into negative (<7 U/mL), positive (≥7–70 U/mL), and strongly positive (≥70 U/mL), that is, 10 times upper limit normal. Results: Fifty-nine children (1.3%) were TG2A positive, and of these 31 (53%) had concentrations 70 U/mL or more. Children with TG2A concentrations 70 U/mL or more were less often infected with CMV (adjusted odds ratio (aOR) 0.38, 95% CI 0.14–0.98, P  = 0.04) and with any of the 3 viruses (aOR 0.38, 95% CI 0.18–0.78, P  < 0.01) than children with TG2A negative concentrations. In addition, children with TG2A concentrations 70 U/mL or more were less often infected with 2 or more viruses than children with TG2A negative concentrations (aOR 0.15, 95% CI 0.03–0.65, P  = 0.01). Conclusions: Both CMV single infection and combined CMV, Epstein-Barr virus and/or herpes simplex virus type 1 infections are inversely associated with strongly TG2A positivity. This may indicate a protective effect of herpesvirus infections in the pathogenesis of celiac disease autoimmunity.